Сетецентрическая оптимизация оперативного обслуживания элементов энергосистемы - Сокол, Е.И.; Гриб, О.Г.; Швец, С.В. (Електротехніка і електромеханіка, 2016)
В статье уделено внимание вопросам использования сетецентрического подхода при формировании активноадаптивной системы оперативного обслуживания элементов энергосистемы в условиях идеологии Smart Grid. Определен точностной критерий отсева вариантов технической реализации этой системы, реализующей концепцию «обслуживания на основе отклика» У статті приділена увага питанням використання сетецентричного підходу при формуванні активно-адаптивної системи оперативного обслуговування елементів енергосистеми в умовах ідеології Smart Grid. Визначений точносний критерій відсіювання варіантів технічної реалізації цієї системи, що реалізує концепцію «обслуговування на основі відклику» Purpose. Development of precision selection criteria of options of technical realization of effective active and adaptive system of expeditious service of elements of a power supply system in the conditions of network-centric management. Methodology. In development of power supply systems their evolution from the elementary forms using elementary network technologies and models of interactions in power to more irregular shapes within the concept of Smart Grid with elements of network-centric character is observed. This direction is based on Internettechnologies of the last generation, and realize models of power activity which couldn't be realized before. Results. The number of possible options of active and adaptive system of expeditious service of elements of a power supply system is usually rather big and it is difficult to choose the acceptable option by direct search. Elimination of admissible options of the technical realization constructed on the principles of a network centrism means application of the theory of multicriteria optimization from a position of discrete programming. The basis of procedure of elimination is made by algorithm of an assessment of system by criterion of accuracy. Originality. The case of an assessment of the precision characteristic of system at restrictions for the set accuracy is connected with need of decomposition of requirements of all system in general and on separate subsystems. For such decomposition the ratios connecting the accuracy of functioning of a separate subsystem with variations of parameters of all system, and also with precision characteristics of subsystems of the lower levels influencing this subsystem are received. Practical value. In the conditions of the network-centric organization of management of expeditious service of elements of a power supply system elimination of options of subsystems when using precision criterion allows to receive the maximum number of essentially possible options of system of service taking into account the accepted service strategy